Alexander (Sandor) Szakats: A Tribute - Vranken, Martin (Victoria University of Wellington Law Review, 2001)
This article is a tribute to Professor Szakáts, an academic at Victoria College Law School (now the Victoria University of Wellington). The author provides a brief summary of Professor Szakáts' early life fleeing Europe in 1948 before arriving in Wellington to become a lawyer. The article then briefly outlines Professor Szakáts' academic contributions in the area of labour law.